The Border Crossed Us : Rhetorics of Borders, Citizenship, and Latina/o Identity - Cisneros, Josue David, 1981- (Book collections on Project MUSE., 2013)
"The Border Crossed Us explores efforts to restrict and expand notions of US citizenship as they relate specifically to the US-Mexico border and Latina/o identity. Borders and citizenship go hand in hand. Borders define a nation as a territorial entity and create the parameters for national belonging. But the relationship between borders and citizenship breeds perpetual anxiety over the purported sanctity of the border, the security of a nation, and the integrity of civic identity. In The Border Crossed Us, Josue David Cisneros addresses these themes as they relate to the US-Mexico border, arguing that issues ranging from the Mexican-American War of 1846-1848 to contemporary debates about Latina/o immigration and border security are negotiated rhetorically through public discourse. He explores these rhetorical battles through case studies of specific Latina/o struggles for civil rights and citizenship, including debates about Mexican American citizenship in the 1849 California Constitutional Convention, 1960s Chicana/o civil rights movements, and modern-day immigrant activism. Cisneros posits that borders--both geographic and civic--have crossed and recrossed Latina/o communities throughout history (the book's title derives from the popular activist chant, "We didn't cross the border; the border crossed us!") and that Latina/os in the United States have long contributed to, struggled with, and sought to cross or challenge the borders of belonging, including race, culture, language, and gender. The Border Crossed Us illuminates the enduring significance and evolution of US borders and citizenship, and provides programmatic and theoretical suggestions for the continued study of these critical issues"--